2015
DOI: 10.1021/jacs.5b09385
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Microstructural Lithium Metal Growth with Electrolyte Salt Depletion in Lithium Batteries Using 7Li MRI

Abstract: Lithium dendrite growth in lithium ion and lithium rechargeable batteries is associated with severe safety concerns. To overcome these problems, a fundamental understanding of the growth mechanism of dendrites under working conditions is needed. In this work, in situ (7)Li magnetic resonance (MRI) is performed on both the electrolyte and lithium metal electrodes in symmetric lithium cells, allowing the behavior of the electrolyte concentration gradient to be studied and correlated with the type and rate of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
190
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(203 citation statements)
references
References 42 publications
6
190
0
Order By: Relevance
“…[12][13][14]17,[22][23][24] Interestingly, the 3d CSI sheds new light on previous bulk metal NMR studies. For instance, in an earlier study, 12 a similar shift difference between NMR peaks was observed at and ⊥ orientations (relative to B 0 ) of the major faces of a thinner metal strip, by carrying out two separate experiments.…”
Section: Csimentioning
confidence: 89%
See 1 more Smart Citation
“…[12][13][14]17,[22][23][24] Interestingly, the 3d CSI sheds new light on previous bulk metal NMR studies. For instance, in an earlier study, 12 a similar shift difference between NMR peaks was observed at and ⊥ orientations (relative to B 0 ) of the major faces of a thinner metal strip, by carrying out two separate experiments.…”
Section: Csimentioning
confidence: 89%
“…Chief among them are the rapidly decaying B 1 inside the metal (Fig.1), and orientation of the bulk metal surface relative to incident B 1 . [9][10][11] Recent studies [12][13][14][15][16][17][18] have overcome these difficulties to demonstrate and highlight bulk metal NMR and MRI, albeit, primarily applied to batteries and electrochemical cells (section S2).…”
Section: Introductionmentioning
confidence: 99%
“…NMR measurements are sensitive to dendrite growth and are also able to resolve different lithium microstructure morphologies through chemical shift measurements (6)(7)(8)(9). MRI approaches provide additional spatial information, allowing specific structural changes to be localized, thereby enhancing the utility of the methods and simplifying interpretation (7,10,11).…”
mentioning
confidence: 99%
“…NMR measurements are sensitive to dendrite growth and are also able to resolve different lithium microstructure morphologies through chemical shift measurements (6)(7)(8)(9). MRI approaches provide additional spatial information, allowing specific structural changes to be localized, thereby enhancing the utility of the methods and simplifying interpretation (7,10,11). Previous work relied on the measurement of 7 Li and 6 Li signals, where the identification of dendrites could be achieved via changes in the intensities and frequencies of the Li-metal signals due to skin-depth effects and susceptibility shifts, respectively (6-10, 12).…”
mentioning
confidence: 99%
See 1 more Smart Citation